Nutritional, Sensory, and Consumer Preference Analysis of Milkifish Fortified with Shrimp Waste Flour - Agustina, Julia; Dhandy, Rahmat; Nugrahaini, Amelia Dwi; Sholihah, Elis Rahmawati Mar’atus; Ismail, Andi Muhammad (International Journal of Technology, Food and Agriculture, 2026)
Shrimp and milkfish are major aquaculture commodities in Sidoarjo; however, shrimp processing produces substantial by-products rich in protein, minerals, and bioactive compounds. Utilizing these by-products as fortifying ingredients for milkfish pempek supports circular-economy practices and enhances functional food development. Three pempek formulations containing 0%, 10%, and 15% shrimp waste flour were prepared and evaluated. Proximate analysis followed AOAC standard methods, while sensory evaluation was performed by 20 semi-trained panelists using a five-point hedonic scale. Data were analyzed using ANOVA and Tukey’s HSD (p < 0.05). Fortification significantly increased protein and ash contents while reducing moisture and carbohydrate levels. The 10% substitution (Product B) provided balanced nutritional enhancement and obtained the highest sensory scores, particularly for texture and color. In contrast, the 15% formulation exhibited lower acceptability due to intensified crustacean aroma and coarser texture. A 10% substitution level optimizes both nutritional quality and sensory acceptance, supporting sustainable utilization of shrimp by-products.